Characteristics of Suicides and Toxicology in a Cohort of Individuals With Opioid Use Disorder. Issue 2 (3rd April 2021) - Pfeifer, Philippe; Nigg-Trawally, Natalie; Bartsch, Christine; Reisch, Thomas
Abstract: Suicide in patients with opioid use disorder (OUD) is a complex issue. In addition to accidental intoxications, a higher prevalence of fatal suicides in patients with OUD can be found compared to the general population. In this study, suicides with a diagnosis of OUD documented in the project "Suicides, A National Survey" were extracted from our data bank. Individuals with a diagnosis of OUD in their medical history were compared to other suicides. The analyses included clinical and demographic factors as well as an investigation of suicide methods and toxicology of psychotropic drugs. For the statistical analyses, we applied chi-square tests and calculated odds ratios. Out of 6, 495 suicide cases in Switzerland between 2000 and 2010, 215 individuals with a medical history of OUD could be identified. Persons in OUD cases were significantly younger than in other suicide cases ( p < .001) and had more frequently a positive history for suicide attempts ( p = .02). In addition, persons in OUD cases were more often female ( p = .076). Intentional self-poisoning with medication was applied more often in individuals with OUD compared to other suicide methods ( p < .001). When self-poisoning with drugs was compared to violent suicide methods, a combination of benzodiazepines with antidepressants was predominantly found. Our study yielded significant characteristics and risk factors for suicides in individuals with OUD. The predominant method of suicide in individuals with OUD was intended self-poisoning by medication. This knowledge is of clinical importance for the monitoring of at-risk individuals with OUD as well as for suicide prevention in this patient group.